Tying Gulliver down: islamic world’s weak states in the face of american hegemonic expansion - Schenoni, Luis L. (Estudios Internacionales, 2010)
This article intends to describe the behaviour of weak states within a context of hegemonic expansion, assuming that, from the crisis and fall of the Soviet Union to the beginning of the Irak War, this is the situation that best describes American offensive policies toward power vacuum situations in regions such as the Middle East. Therefore, the reaction of a representative sample of states in that region (Afghanistan, Iraq, Iran, Libya and Pakistan) will be analyzed in accordance with policies designed in Washington, trying to describe the most important variables of the interaction as well as restraints imposed to sovereignty of these States and the limits to american expansionism in this region. In order to deal with this matter, a discussion on the different responses given by the international relations theories will be intended. After rescuing theoretical thought on weak states from oblivion, we will try to develop an explanation based on a new model of interaction based on realistic premises.